A new configuration of multilevel inverter to generate higher voltage level with lower components - Rajavel, Premkumar; Asokan, Vimala Juliet (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Nowadays, the demand for cleaner and higher quality electricity supply is increasing among various industries and individual consumers. When compared to conventional two-level inverters, multi-level inverters are becoming more and more common, as these inverters deliver high-quality power with fewer harmonics. Here a new multilevel inverter circuit designed with variable direct current (DC) voltage sources is proposed, this circuit requires limited circuit components, and is compared with the other topologies with the same voltage in the output. The proposed topology requires nine switches in order to generate a single-phase 13-level output voltage without connecting to a polarity-generating circuit. The output voltage level and performance parameters associated with the total harmonic distortion (THD) of the voltage level in the output generated by the proposed multilevel inverter or MLI are evaluated in a MATLAB environment. The final simulation results confirm the behavioral accuracy in the proposed topology while creating all the levels. Also, real-time work is done to verify the operation of the inverter and the results are showcased.